Análisis del proceso electro-Fenton como pretratamiento de biomasa producida por la microalga (Chlorella sp) con el fin de mejorar la producción de biocombustible - Rodríguez Rey, Adenys (Universidad Antonio Nariño, 2022)
The world is going through an environmental crisis, one of its consequences is global warming generated by human activities, such as the use of fossil fuels to generate energy. This review addressed the fuel situation in recent years, with an emphasis on biofuels. The different raw materials for the synthesis of biofuels were compared, emphasizing the production from microalgae (Chlorella sp). The biological properties of the microalgae (Chlorella sp) were described, different pretreatments used to generate disruption in the cell wall, which is highly recalcitrant, were compared, this being the main obstacle to overcome in order to improve the production of biofuels. Finally, a perspective of the pretreatment of electro-Fenton in microalgae (Chlorella sp) biomass was presented in order to improve the production of biofuels.